Disparities in Medical Debt Among U.S. Adults with Serious Psychological Distress (Mary Ann Liebert, 2020)
Purpose: To examine indebtedness for medical care among racial and ethnic minorities and people with serious psychological distress (SPD) using a nationally representative sample in the United States. Methods: Using the 2014?2017 Medical Expenditure Panel Survey, we examine medical debt among individuals with SPD. We develop a logistic regression model to estimate the odds of medical debt by SPD status. We stratify the odds of medical debt for those with SPD by insurance type. Results: The results indicate that after controlling for predisposing, enabling, and physical needs factors, those experiencing SPD have double the odds of having medical debt compared with those without SPD. Non-Hispanic blacks had higher odds of medical debt compared with non-Hispanic whites. We find that individuals with SPD covered under private health insurance have double the odds of having medical debts; and those who are uninsured have triple the odds of having medical debt compared with their counterparts without SPD. Conclusion: The findings suggest that odds of medical debt are higher among people with SPD, even when insured. Additional health policy initiatives to address medical debt among those with SPD may be warranted.